English middles and implicit arguments - Bruening, Benjamin (Glossa (London), 2024)
The proper analysis of English middles (Politicians bribe easily) has always been a matter of debate. I argue that they involve three crucial components: (1) A base-generated subject that is interpreted as the logical internal argument; (2) a logical external argument that is not syntactically projected at all; (3) the semantics of an ability modal. Regarding (1), I provide new data indicating that the surface subject of the English middle is not derived by A-movement and has no representation in the VP. I propose that the subject is interpreted as the logical internal argument by means of two mechanisms independently proposed to account for other facts: (a) a head that binds a verb’s internal argument, proposed for implicit arguments by Bruening (2021); and (b) an abstraction rule triggered by certain varieties of Voice in English, proposed to account for properties of the verbal anaphor do so by Bruening (2019). The abstraction rule causes the unexpressed internal argument of the verb to be bound by the base-generated surface subject of the middle. As for the logical external argument, I show that it is present only semantically and not syntactically. Putative binding in both short passives and middles is logophoric, not syntactic. The final component of the analysis is the semantics of an ability modal. English middles are not necessarily generic, they are not necessarily dispositional, they are not necessarily stative, and they do not require adverbs. The middle, like the passive, is a morphosyntactic category, and it is not useful to try to define a “middle semantics” cross-linguistically.